Auditory Cues Alter the Magnitude and Valence of Subjective Sexual Arousal and Desire Induced by an Erotic Video - Pfaus, James G; Zakreski, Ellen (Archives of sexual behavior, 2024)
Although women and men rate their subjective arousal similarly in response to "female-centric" erotic videos, women rate their subjective arousal lower than men in response to "male-centric" videos, which often end with the male's ejaculation. This study asked whether ratings of subjective sexual arousal and desire using the Sexual Arousal and Desire Inventory (SADI) would be altered if this ending was present or absent, and whether including or excluding the accompanying soundtrack would influence the magnitude and direction of the responses. A total of 119 cis-gendered heterosexual undergraduates (59 women and 60 men) viewed an 11-min sexually explicit heterosexual video that ended with a 15-s ejaculation scene. Two versions of the video were created, one with the ejaculatory ending (E+) and one without (E-). Participants were assigned randomly to view one of the two versions with (S+) or without (S-) the accompanying soundtrack, after which they completed the state version of the SADI. Women and men found both sequences without sound less arousing on the Evaluative, Motivational, and Physiological subscales of the SADI relative to the S+ sequences. However, on the Negative/Aversive subscale, women found the E + S- sequence more negative than did men, whereas this difference was not found with sound. Thus, women and men were sensitive to the auditory content of sexually explicit videos, and scenes of sexual intercourse ending with explicit ejaculation increased the Evaluative and Motivational properties of subjective sexual arousal and desire. However, this occurred in women only when the auditory cues signaled a clear and gratifying sexual interaction.
Keywords: Erotica; Humans; Sexual Behavior; Subjective sexual arousal and desire; Female; libido; lidé; Ejaculation; erotika; Visual; Libido; Erotic video; heterosexualita; ženské pohlaví; Male; Heterosexuality; Cues; Auditory; podněty; sexuální vzrušení; mužské pohlaví; Sexual Arousal; sexuální chování